A modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables and a preparation method thereof

CN121517807BActive Publication Date: 2026-10-09JIANGSU CARRETT TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202512025683.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-30
Publication Date
2026-10-09
Estimated Expiration
2045-12-30

AI Technical Summary

Technical Problem

[0005]最后,现有辐照交联技术对多相体系的适应性不足,且工艺本身存在弊端

Benefits of technology

一、本发明实现了回收料的深度活化与高性能利用,通过固相剪切复合处理,在高能球磨的机械力-热协同作用下,有效改善了回收料颗粒表面的惰性状态,增加了其表面活性和反应位点。此过程促进了马来酸酐接枝聚烯烃弹性体与回收料表面的相互作用,同时使有机蒙脱土片层得以剥离和分散,形成结构更为致密的“回收料-相容剂-纳米片层”复合体。这一处理方式为回收料的高比例(25~40份)添加提供了可能,并使其在基体中能够保持良好的力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure IJGCJAAH966HVAAZRJUVHTCRELAAVFCVOZ4PKJFK
    Figure IJGCJAAH966HVAAZRJUVHTCRELAAVFCVOZ4PKJFK
Patent Text Reader

Abstract

The application discloses a modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables and a preparation method thereof. The method comprises the following steps: obtaining a modified regenerated powder by activating and treating recycled cable material, maleic anhydride grafted POE and organic montmorillonite through high-energy ball milling; obtaining a pre-dispersed composite flame retardant by coating aluminum hypophosphite and zinc borate with polymer wax after compounding; and obtaining the product by mixing, cross-linking and granulating the modified regenerated powder, polyolefin elastomer, high-density polyethylene, pre-dispersed flame retardant, epoxy soybean oil and dicumyl peroxide / N,N'-m-phenylene bismaleimide composite cross-linking agent. The application solves the problems of high proportion of recycled material application, balance between flame retardancy and mechanical properties and long-term thermal stability by interface activation of recycled material, synergistic and pre-dispersed flame retardant and cross-linking network construction throughout the interface of multiple phases, and the product is particularly suitable for photovoltaic cables with a rated voltage of 1.8 / 3 kV and below and a long-term working temperature of 150 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cable material technology, specifically, it relates to a modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables and its preparation method. Background Technology

[0002] The rapid development of the solar photovoltaic industry has placed extremely high demands on the durability, safety, and environmental friendliness of supporting cables. DC cables used in photovoltaic power generation systems are exposed to harsh environments such as strong ultraviolet radiation, high temperature, high humidity, and drastic temperature differences for extended periods. Therefore, they must possess comprehensive properties such as excellent flame retardancy, low smoke and non-toxicity, heat aging resistance, and UV aging resistance.

[0003] Currently, irradiated cross-linked low-smoke halogen-free polyolefins are the mainstream technology for photovoltaic cable materials. To implement environmental protection principles and reduce costs, the use of recycled materials in cable materials has become an industry consensus. However, existing technologies face the following unresolved key technical bottlenecks in achieving high-value, high-proportion application of recycled materials: First, the poor interfacial compatibility of recycled materials is a core obstacle restricting their high performance. The industry commonly uses methods such as simple crushing and direct blending or melt granulation of recycled materials. This method mainly relies on diffusion and entanglement in the molten state, making it difficult to effectively break down the aged surface inert layer of the recycled material and achieve deep bonding with the matrix resin. Even with the addition of compatibilizers, in simple melt blending, the compatibilizers are difficult to act uniformly on the entire interface of the recycled material. This often leads to a significant decrease in mechanical properties such as tensile strength and elongation at break when more than 15 parts of recycled material are added, and the interfacial region fails first during long-term thermo-oxidative aging. Therefore, there is an urgent need for a pretreatment method that can achieve deep activation and interfacial reconstruction of recycled materials in the solid state.

[0004] Secondly, traditional metal hydroxide flame retardant systems have inherent defects. To achieve the UL94 V-0 rating, 40-60 parts by weight of magnesium hydroxide or aluminum hydroxide are required. This high loading of such flame retardants severely degrades the material's processing flowability, leading to difficulties in extrusion and inevitably significantly impairing the material's toughness, impact resistance, and elongation at break. Although surface treatments using silane coupling agents can partially improve dispersibility, they cannot fundamentally resolve the inherent contradiction between high loading and overall material performance. Developing novel flame retardant systems that combine high flame retardancy with good compatibility is key to overcoming this bottleneck.

[0005] Finally, existing irradiation crosslinking technologies are not well-suited for multiphase systems and have inherent drawbacks. In complex systems containing recycled materials and high amounts of flame retardants, the networks formed by irradiation crosslinking tend to homogenize, making it difficult to preferentially strengthen the fragile interfaces between the filler and the matrix. These weak interfaces are prone to becoming the source of performance degradation under long-term stress. More importantly, irradiation crosslinking processes rely on expensive electron accelerators, resulting in high equipment investment, high operating energy consumption, safety requirements, and the potential for localized degradation due to uneven irradiation. Therefore, exploring a chemical crosslinking technology that can preferentially strengthen heterogeneous interfaces and is simple to implement is of significant practical importance.

[0006] In summary, there is an urgent need in this field for a systematic and collaborative innovation technology solution that can address the three major challenges of high performance of recycled materials, balance between flame retardant efficiency and overall performance, and interface stability. Summary of the Invention

[0007] To address the aforementioned technical problems, this invention provides a modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables and its preparation method.

[0008] To achieve the above objectives, the technical solution provided by the present invention is as follows: A method for preparing a modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) The recycled low-smoke halogen-free cable material is crushed into particles with a particle size of 1~4mm, and fed into a high-energy ball mill together with maleic anhydride grafted polyolefin elastomer and organomontmorillonite. Under the conditions of ball-to-material ratio (10~20):1 and rotation speed of 300~600 rpm, solid-phase shear activation treatment is carried out at 50~80℃ for 30~90 minutes to achieve interface activation of recycled material particles, exfoliation and dispersion of organomontmorillonite and mechanochemical compounding with compatibilizer, so as to obtain modified recycled powder. The mass ratio of the recycled cable material particles, maleic anhydride-grafted polyolefin elastomer, and organomontmorillonite is (8~12):(1~2):(0.5~1.5). (2) Dry mix aluminum hypophosphite and zinc borate at a mass ratio of (4~6):1, and then mix them with ethylene-acrylate copolymer wax in a high-speed mixer at 110~130℃ for 15~25 minutes to melt and coat the flame retardant particles with polymer wax to obtain a pre-dispersed composite flame retardant. The amount of the ethylene-acrylate copolymer wax used is 8-15% of the total mass of aluminum hypophosphite and zinc borate; (3) By weight, add 25-40 parts of the modified recycled powder obtained in step (1), 25-40 parts of the polyolefin elastomer, and 5-15 parts of the high-density polyethylene to a mixer and melt and plasticize for 5-8 minutes at 140-160°C and 30-50 rpm; then add 30-45 parts of the pre-dispersed composite flame retardant obtained in step (2) and 2-5 parts of epoxidized soybean oil, and mix for 5-1 minutes at 145-165°C and 40-60 rpm. 0 minutes; then, add a composite crosslinking agent composed of 0.3~0.8 parts of dicumyl peroxide and 0.5~1.5 parts of N,N'-m-phenylenebismaleimide, and carry out a crosslinking reaction for 8~15 minutes at 155~170℃ and 60~80 rpm. The modified regenerated powder obtained in step (1) and the pre-dispersed composite flame retardant obtained in step (2) work synergistically to provide a basis for the composite crosslinking agent to construct a stable crosslinking network that spans the multiphase interface; (4) After step (3), add 0.8~1.8 parts of antioxidant and 1.0~2.0 parts of light stabilizer, mix for 2~4 minutes and discharge the material; then use a twin-screw extruder to granulate and dry the mixture at 140~160℃ to obtain the modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.

[0009] Furthermore, in step (1), the grinding balls used in the high-energy ball mill are zirconia ceramic balls, and the diameter ratio of the grinding balls is: 40% with a diameter of 10mm and 60% with a diameter of 5mm. Using zirconia ceramic grinding balls with specific materials and particle size ratios can provide more uniform and efficient shearing force, avoid metal contamination, and ensure the stable quality of modified and regenerated powder.

[0010] Furthermore, in step (1), the organomontmorillonite is an organomontmorillonite modified with quaternary ammonium salts, wherein the quaternary ammonium salts include hexadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride. Organomontmorillonite modified with quaternary ammonium salts exhibits better compatibility with polyolefin matrices and is more easily exfoliated into nanosheets during high-energy ball milling, thereby more effectively improving the mechanical strength and interfacial stability of the modified regenerated powder.

[0011] Furthermore, in step (2), the median particle size D50 of the aluminum hypophosphite is 1~3 μm, and the median particle size D50 of the zinc borate is 2~5 μm. Controlling the specific particle size range of aluminum hypophosphite and zinc borate is beneficial to forming a more compactly packed flame-retardant synergistic system, and to obtaining a more complete and uniform coating layer in melt coating, thereby further improving flame-retardant efficiency and mechanical properties.

[0012] Furthermore, in step (3), the epoxy value of the epoxidized soybean oil is not less than 0.45. Limiting the epoxy value of the epoxidized soybean oil to not less than 0.45 ensures that it has sufficient reactivity as a dispersant and heat stabilizer, which can effectively improve the dispersion uniformity of each component during the mixing process and help improve the thermal stability of the material.

[0013] Further, in step (3), the mass ratio of dicumyl peroxide to N,N'-m-phenylenebismaleimide in the composite crosslinking agent is 1:(1.5~2.5). Controlling the mass ratio of dicumyl peroxide to N,N'-m-phenylenebismaleimide within a certain range allows for an optimal balance between crosslinking density and crosslinking rate, thereby imparting the cable material with the best thermal elongation properties and long-term thermal aging properties.

[0014] This invention also provides a modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables, prepared by the above method. The cable material is suitable for the insulation and sheathing layers of DC cables used in photovoltaic power generation systems with a rated voltage of 1.8 / 3kV and below and a long-term permissible operating temperature of 150℃. Its elongation rate under load during a thermal extension test (200℃, 0.2MPa, 15min) is no greater than 80%, and its permanent deformation rate after cooling is no greater than 8%.

[0015] Furthermore, the cable material, by weight, comprises: 25-40 parts modified recycled powder, 25-40 parts polyolefin elastomer, 5-15 parts high-density polyethylene, 30-45 parts pre-dispersed composite flame retardant, 0.8-2.3 parts composite crosslinking agent, 2-5 parts epoxidized soybean oil, 0.8-1.8 parts antioxidant, and 1.0-2.0 parts light stabilizer. This defines the optimal composition range of the cable material, within which each component can produce the best synergistic effect, ensuring that the overall performance of the material reaches its optimal level.

[0016] Furthermore, the antioxidant is a composite material composed of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:(1.5~2.5). By employing a specific type and ratio of composite antioxidant, the highly efficient synergistic effect of the primary and secondary antioxidants is achieved, significantly improving the long-term thermo-oxidative aging resistance of the cable material.

[0017] Compared with the prior art, the present invention has the following beneficial effects: I. This invention achieves deep activation and high-performance utilization of recycled materials. Through solid-phase shear composite treatment, under the synergistic effect of mechanical force and heat in high-energy ball milling, the inert state of the recycled material particle surface is effectively improved, increasing its surface activity and reaction sites. This process promotes the interaction between maleic anhydride-grafted polyolefin elastomer and the recycled material surface, while simultaneously allowing the organomontmorillonite sheets to be exfoliated and dispersed, forming a more compact "recycled material-compatibilizer-nanosheet" composite. This treatment method makes it possible to add a high proportion (25-40 parts) of recycled material and maintain its good mechanical properties in the matrix.

[0018] II. This invention constructs a synergistic flame retardant system with good processability. By combining "aluminum hypophosphite / zinc borate compound" with "polymer wax melt coating," an organic coating layer is formed on the surface of the flame retardant particles, improving their compatibility and dispersibility with the polyolefin matrix. This "core-shell" structured pre-dispersed composite flame retardant, while ensuring flame retardant efficiency, helps maintain the processing fluidity of the system and mitigates the adverse effects of high filler content on the mechanical properties of the material.

[0019] Third, this invention forms a stable cross-linked structure that strengthens the multiphase interface. The composite cross-linking system using "dicumyl peroxide / DCP" and "N,N'-m-phenylenebismaleimide / BMI" can construct a three-dimensional cross-linked network within the matrix and at the heterogeneous interface through a sequential mixing process. This structure helps improve the material's resistance to deformation and dimensional stability under high-temperature conditions, specifically demonstrating results in a load elongation rate ≤80% and permanent deformation ≤8% in thermal extension tests, making it suitable for long-term operation at 150℃. Detailed Implementation

[0020] The specific embodiments are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Unless otherwise specified, the raw materials and reagents used in the examples are commercially available.

[0021] Example 1 A method for preparing a modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) Waste photovoltaic cable sheathing material, which has been sorted and confirmed to be free of PVC and other halogen contaminants, is crushed into particles with a particle size of 1-4 mm. 80 kg of recycled material particles, 10 kg of maleic anhydride-grafted polyolefin elastomer, and 7.5 kg of organomontmorillonite modified with cetyltrimethylammonium bromide (the mass ratio of the three is 8:1:0.75, falling within the range of (8-12):(1-2):(0.5-1.5) in claim 1) are weighed and fed into a high-energy ball mill. The high-energy ball mill uses zirconia ceramic balls, and the ball diameter ratio is: 40% with a diameter of 10 mm and 60% with a diameter of 5 mm. Under the conditions of a ball-to-material ratio of 15:1 and a rotation speed of 450 rpm, solid-phase shear activation treatment is carried out at 65°C for 60 minutes to obtain modified recycled powder.

[0022] (2) Weigh 80 kg of aluminum hypophosphate (median particle size D50 of 2 μm) and 20 kg of zinc borate (median particle size D50 of 3 μm, mass ratio 4:1) and dry mix them. Then add them together with 12 kg of ethylene-acrylate copolymer wax (12% of the total mass of flame retardant) into a high-speed mixer and stir at 120°C for 20 minutes to fully melt and coat the flame retardant particles with polymer wax, thus obtaining a pre-dispersed composite flame retardant.

[0023] (3) Add 30 kg of the modified recycled powder obtained in step (1), 32 kg of polyolefin elastomer (POE), and 10 kg of high-density polyethylene to a mixer (filling coefficient controlled at 0.72). Melt and plasticize for 6 minutes at 150°C and 40 rpm. Then add 40 kg of the pre-dispersed composite flame retardant obtained in step (2) and 3.5 kg of epoxidized soybean oil (epoxidation value 0.48), and mix for 8 minutes at 155°C and 50 rpm. Then add 1.5 kg of the composite crosslinking agent composed of 0.5 kg of dicumyl peroxide and 1.0 kg of N,N'-m-phenylenebismaleimide (mass ratio 1:2), and carry out the crosslinking reaction for 12 minutes at 162°C and 70 rpm.

[0024] (4) After step (3), add 1.2 kg of antioxidant (composed of 0.5 kg of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester and 0.7 kg of tris(2,4-di-tert-butylphenyl) phosphite) and 1.5 kg of light stabilizer (a complex composed of benzotriazole UV absorber and hindered amine light stabilizer in a mass ratio of 1:1.2), mix for 3 minutes, and then discharge. The mixture is then pelletized and dried underwater at 150°C using a twin-screw extruder to obtain the modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables. The temperature settings from zone 1 to the die head of the twin-screw extruder are: zone 1 140°C, zone 2 145°C, zone 3 150°C, zone 4 155°C, and die head 160°C.

[0025] Example 2 A method for preparing a modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) Waste photovoltaic cable sheathing material, which has been sorted and confirmed to be free of PVC and other halogen contaminants, is crushed into particles with a particle size of 1-4 mm. 120 kg of recycled material particles, 12 kg of maleic anhydride-grafted polyolefin elastomer, and 18 kg of organomontmorillonite modified with hexadecyltrimethylammonium bromide (the mass ratio of the three is 10:1:1.5, falling within the range of (8-12):(1-2):(0.5-1.5) in claim 1) are weighed and fed into a high-energy ball mill. The high-energy ball mill uses zirconia ceramic balls, and the ball diameter ratio is: 40% with a diameter of 10 mm and 60% with a diameter of 5 mm. Under the conditions of a ball-to-material ratio of 20:1 and a rotation speed of 600 rpm, solid-phase shear activation treatment is carried out at 80°C for 30 minutes to obtain modified recycled powder.

[0026] (2) Weigh 90 kg of aluminum hypophosphate (median particle size D50 of 1 μm) and 15 kg of zinc borate (median particle size D50 of 2 μm, mass ratio 6:1) and dry mix them. Then add them together with 15 kg of ethylene-acrylate copolymer wax (14.3% of the total mass of flame retardant) into a high-speed mixer and stir at 130°C for 15 minutes to fully melt and coat the flame retardant particles with polymer wax, thus obtaining a pre-dispersed composite flame retardant.

[0027] (3) Add 40 kg of the modified recycled powder obtained in step (1), 40 kg of polyolefin elastomer (POE), and 15 kg of high-density polyethylene to a mixer (filling coefficient controlled at 0.75). Melt and plasticize for 5 minutes at 160°C and 50 rpm. Then add 45 kg of the pre-dispersed composite flame retardant obtained in step (2) and 5 kg of epoxidized soybean oil (epoxidation value 0.50), and mix for 5 minutes at 165°C and 60 rpm. Then add 2.0 kg of the composite crosslinking agent composed of 0.8 kg of dicumyl peroxide and 1.2 kg of N,N'-m-phenylenebismaleimide (mass ratio 1:1.5), and carry out the crosslinking reaction for 8 minutes at 170°C and 80 rpm.

[0028] (4) After step (3), add 1.8 kg of antioxidant (composed of 0.6 kg of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester and 1.2 kg of tris(2,4-di-tert-butylphenyl) phosphite) and 2.0 kg of light stabilizer (a complex composed of benzotriazole UV absorber and hindered amine light stabilizer in a mass ratio of 1:1.5), mix for 2 minutes, and then discharge. The mixture is then pelletized and dried underwater at 160°C using a twin-screw extruder to obtain the modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables. The temperature settings from zone 1 to the die head of the twin-screw extruder are: zone 1 145°C, zone 2 150°C, zone 3 155°C, zone 4 160°C, and die head 165°C.

[0029] Example 3 A method for preparing a modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) Waste photovoltaic cable sheathing material, which has been sorted and confirmed to be free of PVC and other halogen contaminants, is crushed into particles with a particle size of 1-4 mm. 96 kg of recycled material particles, 8 kg of maleic anhydride-grafted polyolefin elastomer, and 12 kg of organomontmorillonite modified with octadecyltrimethylammonium chloride (the mass ratio of the three is 12:1:1.5, falling within the range of (8-12):(1-2):(0.5-1.5) in claim 1) are weighed and fed into a high-energy ball mill. The high-energy ball mill uses zirconia ceramic balls, and the ball diameter ratio is: 40% with a diameter of 10 mm and 60% with a diameter of 5 mm. Under the conditions of a ball-to-material ratio of 10:1 and a rotation speed of 300 rpm, solid-phase shear activation treatment is carried out at 50°C for 90 minutes to obtain modified recycled powder.

[0030] (2) Weigh 60 kg of aluminum hypophosphate (median particle size D50 of 3 μm) and 15 kg of zinc borate (median particle size D50 of 5 μm, mass ratio 4:1) and dry mix them. Then add them together with 8 kg of ethylene-acrylate copolymer wax (10.7% of the total mass of flame retardant) into a high-speed mixer and stir at 110°C for 25 minutes to fully melt and coat the flame retardant particles with polymer wax, thus obtaining a pre-dispersed composite flame retardant.

[0031] (3) Add 25 kg of the modified recycled powder obtained in step (1), 25 kg of polyolefin elastomer (POE), and 5 kg of high-density polyethylene to a mixer (filling coefficient controlled at 0.68). Melt and plasticize for 8 minutes at 140°C and 30 rpm. Then add 30 kg of the pre-dispersed composite flame retardant obtained in step (2) and 2 kg of epoxidized soybean oil (epoxidation value 0.45), and mix for 10 minutes at 145°C and 40 rpm. Then add 1.05 kg of the composite crosslinking agent composed of 0.3 kg of dicumyl peroxide and 0.75 kg of N,N'-m-phenylenebismaleimide (mass ratio 1:2.5), and carry out the crosslinking reaction for 15 minutes at 155°C and 50 rpm.

[0032] (4) After step (3), add 0.8 kg of antioxidant (composed of 0.3 kg of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester and 0.5 kg of tris(2,4-di-tert-butylphenyl) phosphite) and 1.0 kg of light stabilizer (a complex composed of benzotriazole UV absorber and hindered amine light stabilizer in a mass ratio of 1:1), mix for 4 minutes, and then discharge. The mixture is then pelletized and dried underwater at 140°C using a twin-screw extruder to obtain the modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables. The temperatures of the twin-screw extruder from zone one to the die head are set as follows: zone one 135°C, zone two 140°C, zone three 145°C, zone four 150°C, and die head 155°C.

[0033] Comparative Example 1 (Defective solid-phase shear activation treatment) A method for preparing a low-smoke, halogen-free, flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) The waste photovoltaic cable sheath material that has been sorted and confirmed to be free of PVC and other halogen contaminants is crushed into particles with a particle size of 1~4mm. 80kg of recycled material particles are weighed and set aside (without ball milling).

[0034] (2) Weigh 80 kg of aluminum hypophosphite (median particle size D50 of 2 μm) and 20 kg of zinc borate (median particle size D50 of 3 μm) and dry mix them. Then add them together with 12 kg of ethylene-acrylate copolymer wax into a high-speed mixer and stir at 120°C for 20 minutes to obtain a pre-dispersed composite flame retardant.

[0035] (3) Add 30 kg of recycled material granules obtained in step (1), 32 kg of polyolefin elastomer (POE), and 10 kg of high-density polyethylene to a mixer. Melt and plasticize at 150°C and 40 rpm for 6 minutes. Then add 40 kg of pre-dispersed composite flame retardant and 3.5 kg of epoxidized soybean oil (epoxidation value 0.48) obtained in step (2), and mix at 155°C and 50 rpm for 8 minutes. Then add 1.5 kg of composite crosslinking agent composed of 0.5 kg of dicumyl peroxide and 1.0 kg of N,N'-m-phenylenebismaleimide, and carry out crosslinking reaction at 162°C and 70 rpm for 12 minutes.

[0036] (4) After step (3), add 1.2 kg of antioxidant and 1.5 kg of light stabilizer, mix for 3 minutes and then discharge. The mixture is then pelletized and dried by a twin-screw extruder at 150°C to obtain the comparative cable material.

[0037] Comparative Example 2 (Pretreatment with melt coating lacking flame retardant) A method for preparing a low-smoke, halogen-free, flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) Same as step (1) in Example 1.

[0038] (2) 80 kg of aluminum hypophosphate (median particle size D50 is 2 μm) and 20 kg of zinc borate (median particle size D50 is 3 μm) were directly dry mixed to obtain a composite flame retardant (without melt coating treatment).

[0039] (3) Add 30 kg of the modified recycled powder obtained in step (1), 32 kg of polyolefin elastomer (POE), and 10 kg of high-density polyethylene to a mixer. Melt and plasticize for 6 minutes at 150°C and 40 rpm. Then add 40 kg of the composite flame retardant obtained in step (2) and 3.5 kg of epoxidized soybean oil (epoxidation value 0.48), and mix for 8 minutes at 155°C and 50 rpm. Then add 1.5 kg of the composite crosslinking agent composed of 0.5 kg of dicumyl peroxide and 1.0 kg of N,N'-m-phenylenebismaleimide, and carry out the crosslinking reaction for 12 minutes at 162°C and 70 rpm.

[0040] (4) Same as step (4) in Example 1.

[0041] Comparative Example 3 (lacking a specific composite crosslinking agent) A method for preparing a low-smoke, halogen-free, flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) Same as step (1) in Example 1.

[0042] (2) Same as step (2) in Example 1.

[0043] (3) Add 30 kg of the modified recycled powder obtained in step (1), 32 kg of polyolefin elastomer (POE), and 10 kg of high-density polyethylene to a mixer. Melt and plasticize for 6 minutes at 150°C and 40 rpm. Then add 40 kg of the pre-dispersed composite flame retardant obtained in step (2) and 3.5 kg of epoxidized soybean oil (epoxidation value 0.48), and mix for 8 minutes at 155°C and 50 rpm. Then add 1.5 kg of dicumyl peroxide (single crosslinking agent), and carry out the crosslinking reaction for 12 minutes at 162°C and 70 rpm.

[0044] (4) Same as step (4) in Example 1.

[0045] Comparative Example 4 (Traditional Irradiation Crosslinking Process) A method for preparing a low-smoke, halogen-free, flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) Same as step (1) in Example 1.

[0046] (2) Same as step (2) in Example 1.

[0047] (3) Add 30 kg of modified recycled powder, 32 kg of polyolefin elastomer (POE), and 10 kg of high-density polyethylene obtained in step (1) to a mixer. Melt and plasticize at 150°C and 40 rpm for 6 minutes. Then add 40 kg of pre-dispersed composite flame retardant and 3.5 kg of epoxidized soybean oil (epoxidation value 0.48) obtained in step (2), and mix at 155°C and 50 rpm for 8 minutes. Then add 1.5 kg of triallyl isocyanurate (TAIC, irradiated crosslinking aid), mix for 5 minutes, and then discharge.

[0048] (4) After step (3), add 1.2 kg of antioxidant and 1.5 kg of light stabilizer, mix for 3 minutes and then discharge. The mixture is then pelletized and dried underwater at 150°C using a twin-screw extruder. Subsequently, it is irradiated using an irradiation accelerator with an irradiation dose of 125 kGy to obtain the control cable material.

[0049] Comparative Example 5 (Traditional Metal Hydroxide Flame Retardant System) A method for preparing a low-smoke, halogen-free, flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) Same as step (1) in Example 1.

[0050] (2) Weigh 60 kg of nano magnesium hydroxide (particle size ≤ 1 μm) and 20 kg of micron aluminum hydroxide (particle size 1~3 μm, mass ratio 3:1) and dry mix them. Then mix them with 10 kg of silane coupling agent KH-550 and 8 kg of low molecular weight polyethylene wax in a high-speed mixer at 105 °C for 15 minutes to obtain a surface-activated hydroxide flame retardant.

[0051] (3) Same as step (3) in Example 1, but replace the pre-dispersed composite flame retardant with an equal amount of the hydroxide flame retardant obtained in step (2).

[0052] (4) Same as step (4) in Example 1.

[0053] Comparative Example 6 (Missing multiple core features) A method for preparing a low-smoke, halogen-free, flame-retardant polyolefin cable material for photovoltaic cables includes the following steps: (1) Simply crush the recycled material into particles with a particle size of 1~4mm, weigh 30kg, and set aside (no ball mill, no compatibilizer, no montmorillonite).

[0054] (2) 60 kg of nano magnesium hydroxide and 20 kg of micro aluminum hydroxide were directly dry mixed to obtain a flame retardant (without compounding or coating).

[0055] (3) Put 30 kg of recycled material granules from step (1), 32 kg of polyolefin elastomer (POE), 10 kg of high-density polyethylene, 40 kg of flame retardant obtained from step (2), 3.5 kg of epoxidized soybean oil, and 1.5 kg of dicumyl peroxide (single crosslinking agent) into a mixer at once and mix them at 155°C and 50 rpm for 15 minutes (mixing without order).

[0056] (4) After adding antioxidants and light stabilizers, discharge the material, extrude and granulate, and perform irradiation crosslinking (dose 125kGy).

[0057] Performance comparison tests were conducted on Examples 1-3 and Comparative Examples 1-6, and the test methods are as follows: 1. Tensile strength & elongation at break (test standard ASTM D638) The material is made into a standard dumbbell-shaped specimen and stretched at a constant speed on a universal tensile testing machine until it breaks. Tensile strength is the maximum force per unit area at fracture; elongation at break is the percentage increase in length at fracture relative to the original length.

[0058] 2. Limiting Oxygen Index (LOI, test standard ASTM D2863) The sample was vertically fixed in a glass chimney, and nitrogen-oxygen mixtures of varying concentrations were introduced. The top of the sample was then ignited with a flame. LOI (Lowest Oxygen Intake) refers to the minimum percentage of oxygen required for a material to maintain stable combustion in a nitrogen-oxygen mixture. The higher the value, the more difficult the material is to burn.

[0059] 3. Vertical flammability rating (test standard UL 94) The strip sample is fixed vertically, and its lower end is ignited twice with a Bunsen burner flame of standard height (10 seconds each time). Then, the sample is rated as V-0, V-1, or V-2 based on the afterflame time, afterglow time, and whether burning drips are produced and ignite the cotton below. V-0 is the highest flame retardant rating.

[0060] 4. Thermal stretch test (test standard IEC 60811-507) The sample was placed in a 200°C thermal aging chamber, and a mechanical stress of 0.2 MPa was applied to its lower end for 15 minutes. Elongation under load is the percentage of elongation under heat and pressure; permanent deformation after cooling is the percentage of irreversible elongation after the load is removed and the material is cooled. This test is used to evaluate the resistance of cross-linked cable materials to deformation at high temperatures.

[0061] 5. Retention rate of thermal aging performance (test standard IEC 60811-501) The samples were placed in a thermal aging chamber at 158°C for 168 hours (7 days). After removal, their tensile strength and elongation at break were tested under standard conditions, and the results were compared with the original values ​​before aging to calculate the retention rate. This test is used to evaluate the performance stability of materials under long-term high-temperature use.

[0062] 6. UV aging performance retention rate (test standard ASTM G154) The samples were placed in an ultraviolet aging chamber, using UVA-340 lamps to simulate solar ultraviolet radiation at 0.76 W / m². 2 The material was continuously irradiated for 1000 hours at an ultraviolet radiation level. Afterwards, its elongation at break was measured and compared with the original value before irradiation to calculate the retention rate. This test was used to evaluate the material's resistance to aging under outdoor ultraviolet radiation.

[0063] 7. Melt Flow Rate (MFR, test standard ASTM D1238) A certain amount of material is placed into a barrel heated to a specified temperature (e.g., 190°C). Under the influence of gravity, the molten material is extruded from a capillary tube of standard diameter. MFR refers to the mass (in grams) of material extruded within 10 minutes. This value reflects the flow properties of the material in the molten state, i.e., its processing performance.

[0064] 8. Interface bonding strength A 180° peel test (refer to ASTM D903) is employed. The composite material is fabricated into specific specimens, and its interlayer bonding surface is peeled at a 180° angle. The force required per unit width during peeling is measured. This value directly reflects the interfacial adhesion between recycled materials, flame retardants, etc., and the polymer matrix.

[0065] The test data is shown in the table below: The above test data fully verifies the superiority of the technical solution of the present invention, specifically in the following aspects: 1. The key role of core processes Comparative Example 1, which did not undergo this treatment, showed a significant decrease in its mechanical properties, thermal aging properties, processing fluidity, and interfacial bonding strength. This demonstrates that this process is crucial for breaking the inert layer on the surface of recycled materials, achieving nanocomposite properties, and activating the interface, and is the foundation for achieving high-performance utilization of recycled materials at a high proportion (25-40 parts). Comparative Example 2, whose flame retardant was not coated, saw its vertical flammability rating drop to V-1, and its mechanical properties and processing fluidity deteriorated. This indicates that polymer coating can effectively improve the dispersion of flame retardants, enhance flame retardant efficiency, and mitigate the negative impact on matrix properties. Comparative Example 3, using a single crosslinking agent, showed a significant deterioration in its thermal elongation properties, indicating that N,N'-m-phenylenebismaleimide (BMI) plays an irreplaceable role in constructing a stable crosslinked network spanning the multiphase interface, which is crucial for the dimensional stability of the material at 150°C.

[0066] 2. The advanced nature of the technical solution Comparative Example 4, using traditional irradiation crosslinking, exhibited slightly inferior thermal elongation and interfacial bonding strength compared to the chemical crosslinking system of this invention (Example 1). This demonstrates that the composite crosslinking agent and stepwise mixing process of this invention can more effectively strengthen the multi-element interface while avoiding the problems of high investment and energy consumption in irradiation equipment. Comparative Example 5 employed a traditional magnesium hydroxide / aluminum hydroxide composite flame retardant system. To achieve V-0 flame retardancy, a higher filler content was required, resulting in significantly inferior mechanical properties, processing fluidity (lowest MFR), and elongation at break compared to the aluminum hypophosphite / zinc borate system used in this invention. This directly reflects the inherent contradiction between high filler content and performance degradation in traditional metal hydroxide flame retardant systems.

[0067] 3. Synergistic effect of technological features Comparative Example 6 simulated the "closest prior art," but lacked several core features of this invention. Its test results were completely disastrous, exhibiting the worst performance among all samples, particularly in terms of thermal elongation and performance retention after long-term aging. This strongly demonstrates that the solid-phase shearing, flame-retardant coating, and composite cross-linking techniques of this invention form an organic whole, with significant synergistic effects among them, jointly creating the material's excellent comprehensive performance, rather than being a simple patchwork of technologies.

[0068] In summary, the performance comparison tests fully demonstrate that the three embodiments of the present invention, especially Embodiment 1, achieve excellent levels in all key performance indicators, successfully balancing high recycled material ratio, high flame retardancy, excellent processability, and long-term durability. The performance data of all comparative embodiments are inferior to those of the embodiments to varying degrees, which systematically verifies the necessity of each technical feature in the present invention and the importance of the synergistic effect between different features. These data provide strong support for the novelty, inventiveness, and technological advancement of the patent.

[0069] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. It should not be considered that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables, characterized in that, Includes the following steps: (1) The recycled low-smoke halogen-free cable material is crushed into particles with a particle size of 1~4mm, and fed into a high-energy ball mill along with maleic anhydride-grafted polyolefin elastomer and organomontmorillonite. Under the conditions of ball-to-material ratio (10~20):1 and rotation speed of 300~600 rpm, it is treated at 50~80℃ for 30~90 minutes to obtain modified recycled powder. The mass ratio of recycled cable material particles, maleic anhydride-grafted polyolefin elastomer, and organomontmorillonite is (8~12):(1~2):(0.5~1.5). (2) Dry mix aluminum hypophosphite and zinc borate at a mass ratio of (4~6):1, and then mix them with ethylene-acrylate copolymer wax in a high-speed mixer at 110~130℃ for 15~25 minutes to melt and coat the flame retardant particles with polymer wax to obtain a pre-dispersed composite flame retardant. The amount of the ethylene-acrylate copolymer wax used is 8-15% of the total mass of aluminum hypophosphite and zinc borate; (3) According to the weight parts, 25-40 parts of the modified recycled powder obtained in step (1), 25-40 parts of polyolefin elastomer, and 5-15 parts of high-density polyethylene are put into a mixer and melt-plasticized at 140-160°C and 30-50 rpm for 5-8 minutes; then, 30-45 parts of the pre-dispersed composite flame retardant and 2-5 parts of epoxidized soybean oil obtained in step (2) are added and mixed at 145-165°C and 40-60 rpm for 5-10 minutes; then, a composite crosslinking agent composed of 0.3-0.8 parts of dicumyl peroxide and 0.5-1.5 parts of N,N'-m-phenylenebismaleimide is added and crosslinked at 155-170°C and 60-80 rpm for 8-15 minutes. (4) After step (3), add 0.8~1.8 parts of antioxidant and 1.0~2.0 parts of light stabilizer, mix for 2~4 minutes and discharge the material; then use a twin-screw extruder to granulate and dry the mixture at 140~160℃ to obtain the modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.

2. The method according to claim 1, characterized in that: In step (1), the grinding balls used in the high-energy ball mill are zirconia ceramic balls, and the diameter ratio of the grinding balls is: 40% with a diameter of 10mm and 60% with a diameter of 5mm.

3. The method according to claim 1, characterized in that: In step (1), the organomontmorillonite is an organomontmorillonite modified with quaternary ammonium salt, wherein the quaternary ammonium salt includes hexadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride.

4. The method according to claim 1, characterized in that: In step (2), the median particle size D50 of the aluminum hypophosphite is 1~3μm, and the median particle size D50 of the zinc borate is 2~5μm.

5. The method according to claim 1, characterized in that: In step (3), the epoxy value of the epoxidized soybean oil is not less than 0.

45.

6. The method according to claim 1, characterized in that: In step (3), the mass ratio of dicumyl peroxide to N,N'-m-phenylenebismaleimide in the composite crosslinking agent is 1:(1.5~2.5).

7. A modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables, prepared by the method described in any one of claims 1 to 6.

8. The modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 7, characterized in that: The antioxidant is a complex composed of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:(1.5~2.5).

9. The modified low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 7, characterized in that: The cable material is suitable for the insulation and sheathing layers of DC cables used in photovoltaic power generation systems with a rated voltage of 1.8 / 3kV and below and a long-term allowable operating temperature of 150℃. It is subjected to a thermal elongation test according to IEC 60811-507 standard, held at 200℃ and 0.2MPa load for 15 minutes, with an elongation rate of no more than 80% under load and a permanent deformation rate of no more than 8% after cooling.

Citation Information

Patent Citations

  • Salt corrosion resistant low smoke halogen-free flame-retardant polyolefin elastomers and process for their manufacture

    CN101550248A

  • Fireproof regenerative low smoke zero halogen polyolefin jacket material and preparation method thereof

    CN102924953A